Reliability and validity of the Korean standard pattern identification for stroke (K-SPI-Stroke) questionnaire - Kang Byoung-Kab; Park Tae-Yong; Lee Ju; Moon Tae-Woong; Ko Mi; Choi Jiae; Lee Myeong (BMC, 2012)
Abstract Background The present study was conducted to examine the reliability and validity of the 'Korean Standard Pattern Identification for Stroke (K-SPI-Stroke)', which was developed and evaluated within the context of traditional Korean medicine (TKM). Methods Between September 2006 and December 2010, 2,905 patients from 11 Korean medical hospitals were asked to complete the K-SPI-Stroke questionnaire as a part of project ' Fundamental study for the standardization and objectification of pattern identification in traditional Korean medicine for stroke (SOPI-Stroke). Each patient was independently diagnosed by two TKM physicians from the same site according to one of four patterns, as suggested by the Korea Institute of Oriental Medicine: 1) a Qi deficiency pattern, 2) a Dampness-phlegm pattern, 3) a Yin deficiency pattern, or 4) a Fire-heat pattern. We estimated the internal consistency using Cronbach's α coefficient, the discriminant validity using the means score of patterns, and the predictive validity using the classification accuracy of the K-SPI-Stroke questionnaire. Results The K-SPI-Stroke questionnaire had satisfactory internal consistency (α = 0.700) and validity, with significant differences in the mean of scores among the four patterns. The overall classification accuracy of this questionnaire was 65.2 %. Conclusion These results suggest that the K-SPI-Stroke questionnaire is a reliable and valid instrument for estimating the severity of the four patterns.